Digital Matched Filtering (DMF) Technique for the Performance Enhancement of Few-Mode Fiber Bragg Grating Sensor - Zaini, Muhammad Khairol Annuar; Lee, Yen Sian; Lim, Kok Sing; Ali, Muhammad Mahmood; Nazal, Nurul Asha Mohd; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2019)
In this paper, the digital matched filtering (DMF), a signal processing technique, has been proposed to identify the multiple peak wavelengths more accurately from the reflection spectra of etched few-mode fiber Bragg grating (FM-FBG) sensor. The etched FM-FBG has been fabricated and its intrinsic property of having different sensitivities for different reflection peaks in the spectrum has been used for sensing the multiple parameters, such as temperature and refractive index of the ambient environment. The experimental characterization of the fabricated etched FM-FBG sensor has been carried out by using six samples of standard sodium chloride (NaCl(aq)) solutions with refractive indices (RIs) ranging from 1.3159 to 1.3375 at 24 °C temperature. The reflection spectra have been acquired for each sample by varying the temperature from 24 °C to 80 °C. The temperature and RI sensitivities have been investigated from the acquired spectra by using DMF. The obtained sensor results have been compared with conventional peak detection (CPD) method results for the same spectra. It has been observed that the results obtained by the DMF technique are closer to the reference sensor values and has shown more accuracy than the results obtained by the CPD technique. It has been shown that the DMF has better performance in terms of the accuracy of measured results than that of CPD. In addition, to eliminate the effect of the cross-sensitivity issue of the sensor, the 3 × 3 order characteristic matrix has been used. Hence, the etched FM-FBG can be used as multi-parameter measurements with better performance using the DMF technique.